Q&A Learning New Things and Avoiding Obstacles. - Hoffmann, Leah (Communications of the ACM, 2022)
An interview with University of Tennessee distinguished professor and Association for Computing Machinery (ACM) A.M. Turing Award recipient Jack Dongarra is presented, in which he discusses his internship at the Argonne National Laboratory, the computer software packages EISPACK and LINPACK, and the evolution of computer software design.